2013
DOI: 10.1111/j.1365-2761.2012.01437.x
|View full text |Cite
|
Sign up to set email alerts
|

Florfenicol depletion in edible tissue of rainbow trout, Oncorhynchus mykiss (Walbaum), and sea bream, Sparus aurata L.

Abstract: An increase in fish production has consequently brought an increase in infectious diseases in fish farms. The use of chemotherapic drugs is the most effective instrument against common bacterial agents. The number of registered drugs for use in aquaculture is limited and often veterinary practitioners resort to the off-label use of chemotherapic agents authorized for different food-producing animal species. Florfenicol is well known for its outstanding effect against various pathogenic bacteria affecting fish,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 42 publications
1
16
0
2
Order By: Relevance
“…It is worth emphasizing that the methods reported in the literature for use in residue depletion studies are all based on high performance liquid chromatography with ultraviolet detection, which lacks selectivity. Some studies included an acid hydrolysis step to convert florfenicol and related metabolites to florfenicol amine (Di Salvo et al., ; Gaikowski et al., ; Kosoff et al., and Wrzesinski et al., ). It is also important to highlight that the use of the surrogate florfenicol‐d 3 improved the quality of the data for florfenicol, since this internal standard corrected for the matrix effects associated with the use of mass spectrometry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth emphasizing that the methods reported in the literature for use in residue depletion studies are all based on high performance liquid chromatography with ultraviolet detection, which lacks selectivity. Some studies included an acid hydrolysis step to convert florfenicol and related metabolites to florfenicol amine (Di Salvo et al., ; Gaikowski et al., ; Kosoff et al., and Wrzesinski et al., ). It is also important to highlight that the use of the surrogate florfenicol‐d 3 improved the quality of the data for florfenicol, since this internal standard corrected for the matrix effects associated with the use of mass spectrometry.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the pharmacokinetics of florfenicol and florfenicol amine in fish tissues and plasma after florfenicol administration (Di Salvo et al., ; Feng & Jia, ; Feng et al., ; Gaikowski et al., ; Gaunt et al., ; Wrzesinski et al., ). However, no reports were found concerning the pharmacokinetics or depletion of florfenicol in pacu, with most studies having been performed using Nile tilapia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be attributed to some factors related to changes in pharmacodynamics and pharmacokinetics of drugs in different fish species and also changes in environmental factors such as salt and temperature level of waters (He et al . ; Di Salvo, della Rocca, Terzetti & Malvisi ). In addition to species‐dependent factors, He et al .…”
Section: Discussionmentioning
confidence: 99%
“…Important differences in the frequency and concentration of residues were observed among the fish species tested. This could be attributed to some factors related to changes in pharmacodynamics and pharmacokinetics of drugs in different fish species and also changes in environmental factors such as salt and temperature level of waters (He et al 2012;Di Salvo, della Rocca, Terzetti & Malvisi 2013). In addition to species-dependent factors, He et al (2012) noted that a variety of other factors such as administration routes, period and dosage of antibiotics as well as quantity and harvesting time of fishes may be involved.…”
Section: Discussionmentioning
confidence: 99%